Adding Value to Milk by Increasing Its Conjugated Linoleic Acid Content - Lokenga Badinga; Richard D. Miles (EDIS, 2011)
One of the most promising bioactive components of milk is called conjugated linoleic acid. In laboratory animals, this naturally occurring fatty acid has been shown to inhibit cancer, promote the immune system, reduce the effect of type 2 diabetes, promote bone growth, and reduce blood clotting. This 3-page fact sheet briefly reviews dietary strategies for dairy cows that have been used to increase conjugated linoleic acid concentrations in milk and to show how this approach can be used to add value to milk and milk products. Written by Lokenga Badinga and Richard D. Miles and published by the UF Department of Animal Science, July 2011.